Comparative morphology of scorpion metasomata: Muscles and cuticle. (January 2021) - Günther, Alice; Monod, Lionel; Wirkner, Christian S.
Abstract: Scorpions are among the most popular research objects within Arachnida and there is an impressive body of knowledge about their biology, distribution, morphology, etc. Although the poison sting has gained a lot of attention due to its potential lethal effects to humans, hitherto, there has been no comparative morphological study on the metasoma, the body part that delivers the poisonous injection. The metasoma always consists of five body segments terminated by a poison sting, but it presents significant morphological variations, both between sexes and between species. Its form ranges from long and thin to short and rather reduced to thick and dominant. In this study, we investigated species representing major scorpion clades and most of the known morphological disparity. Using high-resolution micro-computer-tomography and 3D-reconstruction, we present the first 3D visualizations of metasomal exo-skeletal elements in combination with their musculature. Despite of morphological varying metasomal forms, in all investigated species, a repeating pattern of muscles was found: four pairs of muscles in metasomal segment one to four and two pairs of muscles in metasomal segment five. However, the metasomal muscles are characterized by an antero-posterior change in their shapes and sizes and interspecific variation was also found in the extrinsic metasomal musculature, i.e. the muscles that link metasoma to mesosoma. Highlights: Despite morphologically varying metasomal forms, metasomal musculature appears to be quite uniform in scorpions. The common patterns are: 4 pairs on muscles in metasomal segment 1–4, 2 pairs of muscles in metasomal segment 5. Variation occurs in the shape of muscles in an anterior-posterior direction. The extrinsic muscles of the metasoma can show species-specific differences.